Phase II study of gemcitabine plus S-1 chemotherapy in recurrent and metastatic nasopharyngeal carcinoma patients after failure of platinum-based chemotherapy - PeiJian Peng (Therapeutic Advances in Medical Oncology, 2016)
Purpose: No standard salvage regimen has been established for patients with recurrent and metastatic nasopharyngeal carcinoma (NPC) and disease progression after prior platinum-based chemotherapy. This phase II study was designed to evaluate the efficacy and safety of gemcitabine plus S-1 (GS) chemotherapy as a remedial regimen in this setting. Methods: In this multicenter phase II study, 49 patients with recurrent and metastatic NPC who failed previous platinum-based chemotherapy received gemcitabine (1.0 g/m 2 on days 1 and 8) plus oral S-1 chemotherapy (twice daily from day 1 to 14). Each cycle was repeated every 3 weeks for two cycles at least. The dose of S-1 was determined according to the body surface area (BSA): 40 mg twice a day for BSA <1.25 m 2 ; 50 mg twice a day for 1.25 m 2 ⩽ BSA <1.5 m 2 ; and 60 mg twice a day for BSA ⩾1.5 m 2 . Results: Treatment was generally well-tolerated. A total of seven patients (14.3%) had grade 3 toxicities and the main toxicity was myelosuppression, whereas the nonhematology adverse events were minimal. There were 3 complete responses (6.4%), 17 partial responses (36.2%), and the overall response rate was 42.6% (95% confidence interval: 27.3–61.2). Median time to progression was 5.8 months and median survival was 14.8 months. The 1- and 2-year survival rates were 64% and 30%, respectively. Conclusions: Gemcitabine plus S-1 offers a satisfactory clinical activity and an acceptable safety profile for recurrent and metastatic NPC patients after failure of platinum-based chemotherapy.